PENINGKATAN LAJU DISOLUSI CARVEDILOL MELALUI PEMBENTUKAN DISPERSI PADAT MENGGUNAKAN PEMBAWA NATRIUM ALGINAT - Angkasa, Cindy
Carvedilol is a drug compound belonging to Class II of Biopharmaceutical Classification System (BCS) which has low solubility and high permeability. The bioavailability of drug in this class is governed by its solubility and dissolution rate. The preparation of solid dispersion can be use as a selected method to improve of dissolution rate of the active substance. In this study, the effect of solid dispersion formation was studied using sodium alginate as a carrier in various ratios by using solvent evaporation method. Dissolution tests were performed on carvedilol, recrystalized carvedilol in methylene chloride, its physical mixture, and its solid dispersion using dissolution test apparatus type 2 at the temperature of 37 ± 0.5 °C and rotating speed of 50 rpm. The amount of carvedilol dissolved was analyzed using a UV-ð???±®????í????±?±? ?????max of 240 nm. The solid dispersion characterization was performed by using Scanning Electron Microscope (SEM) and Fourier Transform Infrared (FTIR) spectrophotometer. The best dissolution rate of carvedilol was shown by solid dispersion 1:3. The amount of carvedilol dissolved after 30 minutes was 63.21 ± 1.11 % which was higher than pure carvedilol with 22.32 ± 1.59 % carvedilol dissolved on the medium of HCl 0.7% at pH of 1.45. There was no new peak found from FTIR spectrum whereas the morphology study by SEM showed that there was an agglomeration of carvedilol particle on the surface of sodium alginate. The physical mixture and solid dispersion 1:3 were then compressed into tablets by direct compressing method. Tablets of physical mixture and solid dispersion showed an increasing of carvedilol dissolution rate up to 69.93 ± 0.57 % and 75.42 ± 2.61 % respectively.